Federal Government Initiatives and the Foundations of the Information Technology Revolution: Lessons from History - Blumenthal, Marjory S. (American Economic Review, 1998)
There is little argument that early investment in computing and communications (CC guidance for future research policy can come from an examination of history. Whereas a vigorous industry has been visible for decades, many outside observers who question the need for federal C&C research support are often ignorant of the continuing exploitation by industry of science and technologies developed decades ago via past support and how such support has complemented industrial activities. This paper outlines how the organization of federal funding for C&C R&D has helped to make such funding so fertile, noting dimensions that may be of enduring value even as circumstances change. It focuses on the High Performance Computing and Communications Initiative of the 1980's and early 1990's, which evolved from earlier funding programs and influences current programs and prospects.' By design (and reflecting space limitations), the paper emphasizes positive aspects that may be relevant for the future.